IMPLEMENTASI HADITS TARBAWI DALAM PROSES PENDIDIKAN DI SEKOLAH ISLAM - Zjulpi Andriansah; Qonita; Ainul Gani; Guntur Cahaya Kesuma; Amirudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The implementation of tarbawi hadith in the educational process in Islamic schools has a very important role in efforts to develop students' morals and character values. Tarbawi hadith is a collection of hadith containing teachings and moral lessons originating from the words and actions of the Prophet Muhammad SAW. The purpose of this research is to analyze how the Tarbawi Hadith is taught in the Islamic education system, the methods used by teachers, and the impact of these methods on students in cultivating Islamic values. This study uses a qualitative approach using observation, interviews, and literature studies in several Islamic schools. The research findings show that Hadith Tarbawi is implemented with various methods, including silent teaching in religious education, exemplary educators, and internalization in school activities such as group projects, Islamic education, and Islamic-based curriculum. In addition, the use of technology in education also helps increase the effectiveness of the implementation of Hadith Tarbawi in schools. The results of this study indicate that the implementation of Hadith Tarbawi has made a significant contribution in improving religious understanding, developing disciplined character, and improving ethical values ​​in students' daily lives. In order for the understanding and internalization of the hadith to run smoothly, teacher guidance is very important. Therefore, the integration of Hadith Tarbawi in the Islamic education system must continue to be improved in order to be able to produce a noble generation and have high religious knowledge.